Effects of exercise intensity and altered substrate availability on cardiovascular and metabolic responses to exercise after oral carnitine supplementation in athletes - Broad, E. M.; Maughan, R. J.; Galloway, S. D. R. (International Journal of Sport Nutrition and Exercise Metabolism, 2011)
The effects of 15 d of supplementation with L-carnitine L-tartrate (LC) on metabolic responses to graded-intensity exercise under conditions of altered substrate availability were examined. Fifteen endurance-trained male athletes undertook exercise trials after a 2-d high-carbohydrate diet (60% CHO, 25% fat) at baseline (D0), on Day 14 (D14), and after a single day of high fat intake (15% CHO, 70% fat) on Day 15 (D15) in a double-blind, placebo-controlled, pair-matched design. Treatment consisted of 3 g LC (2 g L-carnitine/d; n = 8) or placebo (P, n = 7) for 15 d. Exercise trials consisted of 80 min of continuous cycling comprising 20-min periods at each of 20%, 40%, 60%, and 80% VO2peak. There was no significant difference between whole-body rates of CHO and fat oxidation at any workload between D0 and D14 trials for either the P or LC group. Both groups displayed increased fat and reduced carbohydrate oxidation between the D14 and D15 trials (p < .05). During the D15 trial, heart rate (p < .05 for 20%, 40%, and 60% workloads) and blood glucose concentration (p < .05 for 40% and 60% workloads) were lower during exercise in the LC group than in P. These responses suggest that LC may induce subtle changes in substrate handling in metabolically active tissues when fatty-acid availability is increased, but it does not affect whole-body substrate utilization during short-duration exercise at the intensities studied.